MEMBANGUN USAHA PEDESAAN MELALUI PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (Suatu Kasus di Propinsi Jawa Barat dan Jawa Tengah) - Surachman Suwardi (JIP ( Jurnal Industri dan Perkotaan ), 2011)
The objectives of this study were to analyze the influence partially and simultaneously of capacity bulding activities by Field Extension Workers (FEW/PP), Field Liason Officers (FLO/PMT), and partisipation of Farmers Group Assosiation (Gapoktan) on adoption level on group capacity building program. The study object was a Farmer’s Group Assosiation guided through Rural Agribussines Development Program (RADP/PUAP) in West Java and Central Java Provinces using observation and interview methods. The respondents were 235 farmers chosen by the clusters sampling and disproportionate random sampling. The study was carried out during 2 months beginning from October to November 2010. The data were collected descriptively and verificatively analyzed using the Structural Equation Model (SEM). The results of this study indicated that the first is capacity bulding learning by Agricultural Extension Workers , Field Liason Officers, and member’s partisipation of Farmer’s Group Assosiation influenced significantly partially and simultaneously on adoption level of Farmer’s Group Assosiation on capacity building program ; the second is need a reorientation Capacity Building Design.